2007
DOI: 10.1186/1471-2229-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional characterization of a cDNA coding a hydroxycinnamoyltransferase involved in phenylpropanoid biosynthesis in Cynara cardunculus L

Abstract: BackgroundCynara cardunculus L. is an edible plant of pharmaceutical interest, in particular with respect to the polyphenolic content of its leaves. It includes three taxa: globe artichoke, cultivated cardoon, and wild cardoon. The dominating phenolics are the di-caffeoylquinic acids (such as cynarin), which are largely restricted to Cynara species, along with their precursor, chlorogenic acid (CGA). The scope of this study is to better understand CGA synthesis in this plant.ResultsA gene sequence encoding a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 35 publications
4
86
0
Order By: Relevance
“…Two distinct pathways have been proposed for the synthesis of chlorogenic acid: (1) pathway from p-coumaroyl-CoA, involving first a transesterification of this compound and quinic acid via hydroxycinnamoyl-CoA:quinate hydroxycinnamoyl transferase (HQT) activity and then hydroxylation of p-coumaroylquinate to 5-caffeoylquinic acid, catalyzed by C3 0 H; (2) pathway involving p-coumaroyl-CoA trans-esterification with shikimic acid by means of hydroxycinnamoyl-CoA: shikimate hydroxycinnamoyl transferase (HCT), then p-coumaroylshikimate hydroxylation to caffeoylshikimate. This compound is then converted by HCT (Hoffmann et al 2003;Comino et al 2007) to caffeoyl-CoA which is conjugated to quinic acid by HQT (Niggeweg et al 2004) activity, to give 5-caffeoylquinic acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two distinct pathways have been proposed for the synthesis of chlorogenic acid: (1) pathway from p-coumaroyl-CoA, involving first a transesterification of this compound and quinic acid via hydroxycinnamoyl-CoA:quinate hydroxycinnamoyl transferase (HQT) activity and then hydroxylation of p-coumaroylquinate to 5-caffeoylquinic acid, catalyzed by C3 0 H; (2) pathway involving p-coumaroyl-CoA trans-esterification with shikimic acid by means of hydroxycinnamoyl-CoA: shikimate hydroxycinnamoyl transferase (HCT), then p-coumaroylshikimate hydroxylation to caffeoylshikimate. This compound is then converted by HCT (Hoffmann et al 2003;Comino et al 2007) to caffeoyl-CoA which is conjugated to quinic acid by HQT (Niggeweg et al 2004) activity, to give 5-caffeoylquinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding HCT in globe artichoke has recently been isolated (Comino et al 2007 LG 10 Some CYP98 genes are expressed constitutively, while others (particularly those involved in the stress response) are inducible. A. thaliana CYP98A3 is constitutively expressed and is upregulated by wounding (Schoch et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR conditions applied followed the recommendations of the markers developer and the amplicons were separated in the same way as the AFLPs. SNP markers were directed at seven genes involved in the synthesis of caffeoylquinic acids, namely HCT, HQT, C3'H, C4H, 4CL, Acyltransf_1 and _2 (Comino et al 2007;Moglia et al 2009;Menin et al 2010). The assay was based on a tetra-primer ARMS-PCR (amplification refractory mutation system) protocol (Ye et al 2001), with the amplicons being separated by electrophoresis through 2% w/v agarose gels and visualized by ethidium bromide staining.…”
Section: Genotypic Analysismentioning
confidence: 99%
“…In artichoke, a cDNA coding for HCT has been isolated (Comino et al, 2007). Biochemical characterization suggested that HCT could act either before or after the 3#-hydroxylation step and may contribute to CGA biosynthesis.…”
mentioning
confidence: 99%